KAJIAN PENGELOLAAN KESEJAHTERAAN SATWA DI TAMAN WISATA ALAM PUNTI KAYU PALEMBANG SUMATERA SELATAN - Irwani Gustina Teguh; Burhanuddin Masy'ud; Eva Rachmawati (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
Punti Kayu Natural Recreation Park (TWA Punti Kayu) is located in the city of Palembang, South Sumatra Province and serves as an area preserving the diversity of the species used for tourist activities. In use, Punti Kayu Natural Recreation Park has made animal park. This animal park management should take into account the welfare of animals. There are five principles of animal welfare with regard to wildlife management: (1) freedom from thirst and hunger, (2) freedom from pain, injury and disease, (3) freedom from discomfort, (4) freedom from fear and pressure , and (5) are free to display natural behaviors. The achievement in the implementation of animal welfare of Punti Kayu Animal Park included in the fairly criteria level because it has a average index 1.60 point. Keywords : animal welfare, Punti kayu Nature Park, wildlufe management